2016
DOI: 10.1213/ane.0000000000001188
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin Complex Concentrates for Bleeding in the Perioperative Setting

Abstract: Prothrombin complex concentrates (PCCs) contain vitamin K-dependent clotting factors (II, VII, IX and X) and are marketed as 3 or 4 factor-PCC formulations dependent on the concentrations of Factor VII. PCCs rapidly restore deficient coagulation factor concentrations to achieve hemostasis, but as with all procoagulants, the effect is balanced against thromboembolic risk. The latter is dependent on both the dose of PCCs and individual patient prothrombotic predisposition. PCCs are Food and Drug Administration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 127 publications
(165 reference statements)
1
47
0
3
Order By: Relevance
“…Although specific compositions vary depending on the manufacturer, 4-factor PCCs contain vitamin K–dependent coagulation factors (factors II, VII, IX, and X), the anticoagulant proteins C and S (some also contain antithrombin), and small amounts of heparin. 12 The advantages of PCCs relative to FP are that they are pathogen reduced, do not require ABO blood group matching or thawing (allowing for near-patient storage and timely administration), are manufactured from pooled plasma (decreasing the risk of transfusion-related acute lung injury), require substantially lower volumes to achieve dose equivalence with FP (decreasing the risk of transfusion-associated circulatory overload), and may lead to greater thrombin generation (improving hemostatic effectiveness). 12 , 13 , 14 , 15 On the other hand, because PCCs do not contain the full, balanced complement of procoagulants and anticoagulants that are present in FP, they may be less effective in restoring hemostasis, may carry a higher thrombosis risk (possibly owing to an imbalance in factor II to antithrombin ratio), or both.…”
Section: Introductionmentioning
confidence: 99%
“…Although specific compositions vary depending on the manufacturer, 4-factor PCCs contain vitamin K–dependent coagulation factors (factors II, VII, IX, and X), the anticoagulant proteins C and S (some also contain antithrombin), and small amounts of heparin. 12 The advantages of PCCs relative to FP are that they are pathogen reduced, do not require ABO blood group matching or thawing (allowing for near-patient storage and timely administration), are manufactured from pooled plasma (decreasing the risk of transfusion-related acute lung injury), require substantially lower volumes to achieve dose equivalence with FP (decreasing the risk of transfusion-associated circulatory overload), and may lead to greater thrombin generation (improving hemostatic effectiveness). 12 , 13 , 14 , 15 On the other hand, because PCCs do not contain the full, balanced complement of procoagulants and anticoagulants that are present in FP, they may be less effective in restoring hemostasis, may carry a higher thrombosis risk (possibly owing to an imbalance in factor II to antithrombin ratio), or both.…”
Section: Introductionmentioning
confidence: 99%
“…Other four component PCCs available in most countries include both Beriplex P/N and Octaplex (Octapharma, Vienna, Austria), and others is listed in table 1. (5, 4648) Multiple international guidelines recommend the use of four component PCCs rather than plasma or fresh frozen plasma as a primary treatment for the emergent reversal of warfarin. (5) Advantages of PCCs for acute warfarin reversal include ease of storage, rapid INR correction, small infusion volume (~20 ml per 500IU), and viral inactivation and/or nanofiltration.…”
Section: Clinical Studies Evaluating the Role Of Fibrinogen Replacementmentioning
confidence: 99%
“…(5, 4648) Multiple international guidelines recommend the use of four component PCCs rather than plasma or fresh frozen plasma as a primary treatment for the emergent reversal of warfarin. (5) Advantages of PCCs for acute warfarin reversal include ease of storage, rapid INR correction, small infusion volume (~20 ml per 500IU), and viral inactivation and/or nanofiltration. (5) One report from the United Kingdom National Health Service suggested that PCCs for emergency warfarin reversal were more cost-effective than plasma.…”
Section: Clinical Studies Evaluating the Role Of Fibrinogen Replacementmentioning
confidence: 99%
See 2 more Smart Citations